P368 Proactive Therapeutic Drug Monitoring is more effective than Conventional Management in Inducing Fecal Calprotectin remission in Inflammatory Bowel Disease. (27th May 2021) - Pedro, J; Rodrigues, I; Fernandes, S; Gonçalves, A R; Bernardo, S; Baldaia, C; Valente, A; Moura Santos, P; Correia, L; Tato Marinho, R
Abstract: Background: Proactive therapeutic drug monitoring (pTDM) may potentially improve disease control and treatment outcomes in inflammatory bowel disease. Methods: Using a prospectively maintained database we compared 135 patients following a pTDM protocol aiming at an Infliximab trough level (IFXTL) between 5-10 µg/mL with sequential measurements of Fc, with 108 patients from a retrospective group under conventional management (noTDM). We evaluated the rates of Fc remission (<250 µg/g), and other clinical outcomes at 2-years of follow up. Results: pTDM associated with higher rates of Fc remission (69.6% vs 50.0%; P =0.002), and steroid-free clinical remission (78.4% vs 55.2%, P =0.028) with a trend for clinical remission (79.3% vs 68.5%, P =0.075). There was no difference in treatment discontinuation ( P =0.195), hospitalization ( P =0.156), and surgery ( P =0.110). Higher IFXTL associated with Fc remission at week 14 (6.59 vs 2.96 µg/mL, P <0.001), and at the end follow-up (8.10 vs 5.03 μg/mL, P =0.001). Fc remission associated with higher rates of clinical remission (85.8% vs 56.8% P <0.001), steroid-free clinical remission (86.9% vs 50.0% P <0.001), and lower rates of IFX discontinuation (8.8% vs 36.8%, P <0.001), and hospitalization (13.5% vs 33.7%, P <0.001) with a non-significant trend for surgery (6.1% vs 12.6%, P =0.101). Conclusion: PTDM was more effective than conventional management in inducing Fc remission which associated with improved clinical outcomes.